BIOGRAFI BAINUR : PEJUANG MEMPERTAHANKAN KEMERDEKAAN DARI LASKAR SABIL MUSLIMAT DI FRONT PADANG AREA (1945-1947) - Ayu, Delvia Sari; Husnita, Liza; Erawati, Meri (Pendidikan Sejarah, 2013)
ABSTRACTÂ This paper discusses about Bainur in saving freedom of Indonesia ( 1945-1947).Â  Bainur is a hero figure coming from religion and simple family.Â  She is got the eduction from citizen scool , thus, indirectly it had grown the nationalism for herself.Â  Journey of bainur in saving the freedom of indonesia specially Padang city,itâs begun when she join with woman soldier Â such as KRI, PERWARI, etc. Bainur followed laskar Sabil Muslimat.Â  which recruit its member from sticks of Nasyiatul Aisyiah, in membershipÂ  center of laskar Sabil Muslimat , her get to domicile asÂ  proxy of sie i,Â  while in stickly / his hostel represent one of the head of hostel of laskar Sabil Muslimat, and in companyly his have been assigned by at red cross company andÂ  security/ investigator. Method which writer use in writing of this research isÂ  historicalÂ  method with a few step. First step isÂ  heuristic, that is collecting relevant data. The Second is criticism source of representing phase examination of source or data Third step, that is data interpretation,. And which to four that is or historiografi of discribing data in the form of article of science. The conlusion is based on the result of the research in dutch period in Indonesia, Bainur ever followed the military training and education of war in laskar Sabil Muslimat, based on his experience she was strong to save his birth land from the dutch in freedom 1945-1947. Keywords: Role, People, Biography, Warrior, Hero, Sabil Muslimat, War of Independence